Hubungan Komunikasi Terapeutik Perawat Dengan Kepuasan Keluarga Pasien Di Ruang Intensif RSUD dr. Doris Sylvanus - Saw Billa, Admi; Carolina, Putria; Frisilia, Melisa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
The intensive care room is a treatment unit in a hospital that specializes in managing patients in critical condition or serious illness, injuries with life-threatening complications, which require trained personnel supported by special equipment. Nurses' therapeutic communication can help patient families understand the situation and increase satisfaction. The phenomenon that occurs is that the patient's family is dissatisfied because the nurses are less informative, which shows that there are still nurses who do not communicate therapeutically well. Nurse therapeutic communication is the nurse's ability and skills in interacting and conveying information to patients and their families, so that patients and families can adapt to the problems they face. Patient family satisfaction is an expression of feelings of joy or disappointment experienced by the patient's family after their family members receive health services. This study aims to determine the relationship between nurses' therapeutic communication and patient family satisfaction. This research design uses a correlational design with a cross-sectional approach. The sampling technique was purposive sampling with a total of 40 respondents. Based on the Spearman Rank test results, it was found that p value = 0.000 or a significance level of p < 0.05, then Ha was accepted so that there was a relationship between nurse therapeutic communication and patient family satisfaction in the intensive room at RSUD dr. Doris Sylvanus.